1994
DOI: 10.1037/0022-006x.62.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Patient pretreatment interpersonal problems and therapeutic alliance in short-term cognitive therapy.

Abstract: The growing consensus regarding the importance of interpersonal process in psychotherapy, as well as of interpersonal factors in self-definition, has underscored the relevance of examining patient interpersonal functioning as it relates to the development of the therapeutic alliance. This study examined the relationship of patient pretreatment interpersonal functioning (as measured by the Inventory of Interpersonal Problems and the Million Clinical Multiaxial Inventory) to the therapeutic alliance (as measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
6
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 18 publications
14
147
6
2
Order By: Relevance
“…For example, interpersonal problems influence the development of the therapeutic alliance, with friendly-submissive patients being able to form an alliance much easier than cold-dominant patients (Muran et al, 1994). Similarly, several research studies have also shown that friendly-submissive interpersonal problems are positively related to psychotherapy outcome, whereas cold-dominant interpersonal problems are negatively related to outcome in both cognitive-behavioral and psychodynamic therapy (Borkovec et al, 2002;Horowitz et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, interpersonal problems influence the development of the therapeutic alliance, with friendly-submissive patients being able to form an alliance much easier than cold-dominant patients (Muran et al, 1994). Similarly, several research studies have also shown that friendly-submissive interpersonal problems are positively related to psychotherapy outcome, whereas cold-dominant interpersonal problems are negatively related to outcome in both cognitive-behavioral and psychodynamic therapy (Borkovec et al, 2002;Horowitz et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Third, we examined subtype differences on posttreatment measures of general symptom severity, level of social anxiety, psychological well-being, level of optimism, and satisfaction with social functioning. Extensive research using the IIP-C has shown that friendly-submissive interpersonal problems are positively related to psychotherapy outcome, whereas hostile-dominant problems are negatively related to outcome (e.g., Gurtman, 1996;Horowitz et al, 1992;Horowitz, Rosenberg, & Bartholomew, 1993;Kasoff & Pincus, 2002;Muran et al, 1994). Therefore, we predicted that socially phobic patients with friendly, exploitable, and submissive interpersonal problems would respond more positively to psychotherapy than socially phobic patients with avoidant, cold, and hostile interpersonal problems.…”
Section: This Studymentioning
confidence: 98%
See 2 more Smart Citations
“…[28][29][30] There is also evidence suggesting that personality dysfunction is associated with better treatment outcome in supportive and cognitive-behavioral interventions, 31-32 particularly when considered in the context of presenting distress. 33 Taken together, these data suggest that while many diagnosable Axis II conditions interfere with treatment efficacy, a certain degree of avoidant or submissive personality characteristics (of the kind associated with interpersonal sensitivity) may actually serve to augment benefit from interventions via a number of pathways (discussed in detail in the discussion section).…”
Section: Interpersonal Sensitivity and Psychological Interventionsmentioning
confidence: 99%